2004
DOI: 10.1016/j.chroma.2004.08.042
|View full text |Cite
|
Sign up to set email alerts
|

Determination of folic acid in tablets by microemulsion electrokinetic chromatography

Abstract: A microemulsion electrokinetic chromatography (MEEKC) method has been developed and validated for the determination of folic acid, a water-soluble vitamin, in a commercial tablet formulation. The analysis was performed using a microemulsion containing 0.5% (w/w) ethyl acetate, 1.2% (w/w) butan-1-ol, 0.6% (w/w) sodium dodecyl sulfate, 15% (v/v) 2-propanol and 82.7% (w/w) 10 mmol L(-1) sodium tetraborate aqueous buffer at pH 9.2. Direct UV detection at 214nm led to an adequate sensitivity without interference fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 15 publications
0
26
0
Order By: Relevance
“…The terms folic acid and folates are often used interchangeably, but folic acid is approximately twice as bioavailable as the folates [3]. Analytical methods for folic acid include bioassays [4], enzymatic methods [5], fluorimetry [6][7][8][9][10][11][12][13], spectrophotometry [14][15][16], chromatography [17][18][19][20][21][22][23][24][25], chemiluminescence [26][27][28], phosphorimetry [29] and inductively coupled plasmaatomic emission spectroscopy [30]. Electrochemical methods have been used to detect folic acid [31][32][33][34][35][36][37][38][39][40][41][42] and to investigate its redox properties [43].…”
Section: Introductionmentioning
confidence: 99%
“…The terms folic acid and folates are often used interchangeably, but folic acid is approximately twice as bioavailable as the folates [3]. Analytical methods for folic acid include bioassays [4], enzymatic methods [5], fluorimetry [6][7][8][9][10][11][12][13], spectrophotometry [14][15][16], chromatography [17][18][19][20][21][22][23][24][25], chemiluminescence [26][27][28], phosphorimetry [29] and inductively coupled plasmaatomic emission spectroscopy [30]. Electrochemical methods have been used to detect folic acid [31][32][33][34][35][36][37][38][39][40][41][42] and to investigate its redox properties [43].…”
Section: Introductionmentioning
confidence: 99%
“…Many reports on O/W MEEKC concluded that variations in the nature and concentration of oils, organic modifier and surfactant had a noticeable effect on separation [38][39][40]. Similarly, the above three factors were also utilized to improve MEEKC separations.…”
Section: O/w Meekcmentioning
confidence: 96%
“…The accuracy of the method (% recovery) was found to be 101-106% for ragaglitazar and 101-125% for arginine, while precision for the detection of peaks (% RSD) was found to be 0.63% for ragaglitazar and 3.50% for arginine. An MEEKC method was used for the quantitative determination of folic acid in tablets [137] giving a precision of ,1.2% RSD and recovery of 99.8 6 1.8% at three concentration levels.…”
Section: Determination Of Pharmaceutical Contentmentioning
confidence: 99%